Cohesion policy and metropolitan governance: innovation in stakeholders collaboration practices in Lisbon - Margarida Queirós; Luís Balula; Mário Vale (Boletín de la Asociación de Geógrafos Españoles)
This study examines the impact of Cohesion Policy on metropolitan governance and stakeholders’ collaboration practices in the Lisbon region. The financial crisis and subsequent austerity policies have underscored the importance of institutional arrangements and governance processes, particularly at the local and regional levels. Focusing on the Lisbon metropolitan area, which faces fragmented institutional structures and governance challenges, this research highlights the role of Cohesion Policy through Integrated Territorial Investments (ITI) in fostering innovation and collaboration among stakeholders. The EVA (Green and Blue Corridor) project in the Lisbon Metropolitan Area exemplifies the role of EU funding in promoting cooperation and governance innovation. The introduction of ITI under the Cohesion Policy has facilitated the establishment of collaborative networks and innovative practices in the metropolitan area. These initiatives have broken down planning silos, promoting "soft spaces of governance" that encouraged knowledge exchange and institutional learning among territorial stakeholders. However, challenges persist in the absence of a coherent regional strategy and the prioritization of broad EU objectives over tailored regional needs. This hampers the potential for integrated and proactive territorial management. Nevertheless, Cohesion Policy has stimulated stakeholder collaboration and innovation in metropolitan governance, paving the way for sustainable and inclusive development in the Lisbon region.